Nouveaux modèles de formation et enseignement supérieur : l’exemple du tutorat à l’université - Emmanuelle Annoot (Éducation et Socialisation)
In 1998, tutoring was made official in all French universities by a decree of the Ministry of Education. Tutoring as a methodological and pedagogical support is based on the students coming on a voluntary basis and can vary in its application. Numerous studies have outlined the benefits and limitations of tutoring. It will be useful to expose their main conclusions. In 2007, cl multi-year plan to help students get a degree, entitled « Plan licence » (degree Plan) was launched. The law of August 10 2007 on the freedoms and responsibilities of universities gives to the institutions of higher education a new mission as regards guidance and professional integration. In this institutional framework, « tutoring » as a function is no longer exclusively reserved for students since teachers are required to help students individually (with the concept of academic advisor). This assistance occurs at several stages of the student’s progress (support for orientation, for undergraduate adaptation, step by step progression in a renewed degree, support for finding a job) in relationship with goals set according to the level of achievement to be reached by the student in the course of his studies (skills specific to subjects and generic skills). An updated definition of student tutoring in the new provisions of the « plan licence » will be attempted. This article therefore aims to show how the « plan licence », launched in December 2007, has redefined the role of tutoring in academic courses, this device becoming an element of institution policy designed to promote student success as early as their last year in high school. The writer will wonder about the role of a scientific discourse in the definition and analysis of these public policies. She will rely on the synthesis of a set of research works on tutoring developed with the National Institute of Educational Research (1997-2001) then with the C.N.C.R.E. (1998-2000) and an ongoing programme called « Training, qualification, employment », led within the Greater Research Network « Culture and Society in Normandy ». Finally she will ask questions about the analysis of the effects of these policies in terms of the objectives set and she will specify, in conclusion, how this theme engenders research themes essential to understand the recent changes in French universities.